2011
DOI: 10.1016/j.taap.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Is the PentaBDE replacement, tris (1,3-dichloro-2-propyl) phosphate (TDCPP), a developmental neurotoxicant? Studies in PC12 cells

Abstract: Organophosphate flame retardants (OPFRs) are used as replacements for the commercial PentaBDE mixture that was phased out in 2004. OPFRs are ubiquitous in the environment and detected at high concentrations in residential dust, suggesting widespread human exposure. OPFRs are structurally similar to neurotoxic organophosphate pesticides, raising concerns about exposure and toxicity to humans. This study evaluated the neurotoxicity of tris (1,3-dichloro-2-propyl) phosphate (TDCPP) compared to the organophosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
236
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(248 citation statements)
references
References 71 publications
11
236
1
Order By: Relevance
“…Chlorinated organophosphates, such as tris(2-chloroethyl) phosphate (TCEP), tris(2-chloro-isopropyl) phosphate (TCPP), and tris(2-chloro, 1-chloromethyl-ethyl) phosphate (TDCP) are suspected carcinogens (World Health Organization, 1998). Additionally, TCEP has been linked with incidents of acute death of dogs (Lehner et al, 2010), while TDCP was shown to be more neurotoxic than TCEP and TCPP (Dishaw et al, 2011). Tricresyl phosphate (TCrP), triphenyl phosphate (TPhP), and TDCP are considered as possibly toxic for reproduction (van der Veen and de Boer, 2012;Meeker and Stapleton, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorinated organophosphates, such as tris(2-chloroethyl) phosphate (TCEP), tris(2-chloro-isopropyl) phosphate (TCPP), and tris(2-chloro, 1-chloromethyl-ethyl) phosphate (TDCP) are suspected carcinogens (World Health Organization, 1998). Additionally, TCEP has been linked with incidents of acute death of dogs (Lehner et al, 2010), while TDCP was shown to be more neurotoxic than TCEP and TCPP (Dishaw et al, 2011). Tricresyl phosphate (TCrP), triphenyl phosphate (TPhP), and TDCP are considered as possibly toxic for reproduction (van der Veen and de Boer, 2012;Meeker and Stapleton, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Limited toxicological information indicates that TDCPP may act as an endocrine disruptor (Dishaw et al, 2011;Liu et al, 2013a). adrenocortical carcinoma cells (H295R) exposed to TDCPP have abnormal sex hormone levels (Liu et al, 2012); (2) TDCPP can act as an androgen receptor antagonist (Kojima et al, 2013) and (3) TDCPP can act as an estrogenic receptor (ER) ␣ agonist with estrogenic activity .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that several OP esters cause developmental toxicity and endocrine disruption in vivo and in vitro (Crump et al, 2012;Dishaw et al, 2012;Farhat et al, 2013;Fu et al, 2013;Liu et al, 2012bLiu et al, , 2013McGee et al, 2012McGee et al, , 2013Wang et al, 2013). For example, exposure of zebrafish embryos to tris(1,3-dichloro-2-propyl) phosphate (TDCPP) disrupted embryogenesis and caused larval malformation, with median lethal concentrations (LC 50 ) ranging from 3.7 to 7.0 mg/L (Fu et al, 2013;Liu et al, 2013;McGee et al, 2012;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%